Prevalence of Childhood Trauma and its Relationship with Psychological Resilience among Undergraduate Nursing Students in North India - Neeta Austin Singha; Navita Gupta; Sandeep Kumar Goyal (Indian Journal of Social Psychiatry)
Background: The evaluation of Childhood trauma (CT) rates among nursing students is important as the repercussions of childhood trauma on nursing students might affect not only the individual students but also the patients that he or she may care for. Aims and Objective: 1) To evaluate the prevalence of CT among nursing students 2) To determine the relationship between CT and psychological resilience among nursing students 3) To assess the contributing factors of CT among nursing students. Methods: The present descriptive cross-sectional study involved 1326 nursing students who had been selected using a non-probability method. Childhood trauma was measured with the Childhood Trauma Questionnaire (CTQ) and Resilience was weighed using Connor-Davidson Resilience Scale (CD-RISC). Descriptive statistics, Pearson chi-square tests, and independent samples t-tests were used to analyze the data. Results: Around two-thirds (65%) of the nursing students reported exposure to some type of childhood trauma. More than half (58.2%) students were exposed to more than one type of CT and 8.6% experienced all five forms of CT. Out of five types of traumas, majority of the students experienced emotional neglect. CT was shown to be inversely related to psychological resilience. CT subscales also exhibited a statistically significant negative link with psychological resilience. Conclusion: Childhood trauma is common among nursing students. For the development of trauma-informed interventions, the findings of this study have important ramifications for nursing educators.